2014
DOI: 10.1111/are.12615
|View full text |Cite
|
Sign up to set email alerts
|

Co-culture of sea cucumber Holothuria scabra and red seaweed Kappaphycus striatum

Abstract: Commercially valuable sea cucumbers are potential co-culture species in tropical lagoon environments, where they may be integrated into established aquaculture areas used for seaweed farming. In the current study, wild-caught juvenile sea cucumbers, Holothuria scabra, and red seaweed Kappaphycus striatum were co-cultured on Zanzibar, United Republic of Tanzania. Sea cucumbers (97 g AE 31 SD, n = 52) were cultured in mesh enclosures at initial cage stocking densities of 124 AE 21 SD and 218 AE 16 SD g m À2 unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 38 publications
1
10
2
1
Order By: Relevance
“…Similar results were obtained by Uthicke (2001) and Wolkenhauer et al (2010), who observed that sea cucumbers enhance productivity of primary producers through their burrowing and nutrient recycling activities. In contrast to Beltran-Gutierrez et al (2014), where a low stocking density (154 g m −2 ) of H. scabra yielded higher growth rates of Kappaphycus striatum than either a density of 200 g m −2 or an absence of sea cucumbers, in the current study higher stocking densities of H. scabra (200 and 300 g m −2 ) resulted in the highest growth grates of E. denticulatum. Potential reasons are discussed in the section on the effect of stocking density below.…”
Section: Survival and Growth Of Eucheuma Denticulatumcontrasting
confidence: 96%
See 4 more Smart Citations
“…Similar results were obtained by Uthicke (2001) and Wolkenhauer et al (2010), who observed that sea cucumbers enhance productivity of primary producers through their burrowing and nutrient recycling activities. In contrast to Beltran-Gutierrez et al (2014), where a low stocking density (154 g m −2 ) of H. scabra yielded higher growth rates of Kappaphycus striatum than either a density of 200 g m −2 or an absence of sea cucumbers, in the current study higher stocking densities of H. scabra (200 and 300 g m −2 ) resulted in the highest growth grates of E. denticulatum. Potential reasons are discussed in the section on the effect of stocking density below.…”
Section: Survival and Growth Of Eucheuma Denticulatumcontrasting
confidence: 96%
“…For example, co-culture of H. scabra with shrimp Litopenaues stylirostris is not viable and survival of H. scabra in such a system has been observed to be very low (Bell et al 2007). On the other hand, in an integrated system of the seaweed K. striatum and H. scabra, seaweed did not appear to have a negative effect on sea cucumbers (Beltran-Gutierrez et al 2014).…”
Section: Survival Growth and The Effect Of Stocking Density On H Scmentioning
confidence: 72%
See 3 more Smart Citations